Salusin-α levels are negatively correlated with diastolic blood pressure in children with obesity. (October 2019) - Dervişoğlu, Pınar; Elmas, Bahri; Kösecik, Mustafa; İşgüven, Şükriye P.; Büyükavcı, Mustafa; Köroğlu, Mehmet
Abstract: Salusins have emerged as a new biomarker that reflects an increased inflammatory state, which is associated with cardiovascular risk. We investigated the predictive value and usefulness of salusins as an inflammatory biomarker in obese children. This prospective cohort study included 75 obese children and 101 healthy children (as a control group). Salusin-α, Salusin-β, and various cardiovascular parameters were assessed in both groups. Correlation analyses of Salusin-α and Salusin-β with body mass index standard deviation scores and inflammatory and cardiovascular markers were performed. The mean patient age was 11.9±2.4 years for the obese group and 12.5±2.1 years for the control group. The obese children had a significantly higher heart rate, systolic blood pressure, diastolic blood pressure, epicardial adipose tissue thickness, and left ventricular mass than did the children in the control group. There was no significant correlation between Salusin-α and Salusin-β and body mass index; however, there was a negative correlation between Salusin- α and diastolic blood pressure (r = 0.277, p = 0.004). Overall, there was no significant difference in the Salusin-α and Salusin-β levels between obese and healthy children. However, a negative correlation was found between Salusin-α and diastolic blood pressure. Although this result suggests that Salusin-α might be an early marker of cardiovascular involvement in obese children, further studies are needed to demonstrate the predictive value of salusins.